Neurons populating the rectal extrinsic nerves in humans express neuronal and Schwann cell markers. Issue 7 (31st December 2020) - Woods, Crystal; Kapur, Raj P.; Bischoff, Andrea; Lovell, Mark; Arnold, Michael; Peña, Alberto; Flockton, Amanda; Sharkey, Keith A.; Belkind‐Gerson, Jaime
Abstract: Background: In mice, Schwann cell (SC) progenitors give rise to autonomic ganglion cells and migrate into the gut to become enteric neurons. It is unknown whether SC progenitors have a similar fate in humans. In search of evidence for human SC‐derived neurogenesis in the gastrointestinal (GI) tract, we studied the rectums from cadaveric controls and children with anorectal malformations (ARM). Methods: We analyzed distal rectal tissue taken at autopsy from 10 children with normal GI tracts and resected rectal specimens in 48 cases of ARM. Of these specimens, 6 had neurons within the extrinsic rectal innervation. These were further investigated with immunohistochemistry for neuronal and SC/glial markers. Key Results: Perirectal tissue from control and ARM contained GLUT1‐positive extrinsic nerves, many containing neurons. SC/glial markers (SOX10, CDH19, and PLP1) were expressed by glia in the enteric nervous system and perirectal nerves, while MPZ predominated only in glia of perirectal nerves, in both control and ARM. Neurons in perirectal nerves were 61% larger in ARM samples and co‐expressed SOX10 (81%), PLP1 (73%), and CDH19 (56%). In ARM, cytoplasmic SOX10 was co‐expressed with neuronal antigens in 57% of submucosal and myenteric neurons, vs. 3% in control. Furthermore, intrinsic gut neurons in ARM specimens co‐expressed PLP1 (18%) and CDH19 (18%); however, neuronal co‐expression of PLP1 and CDH19 was rarely (<2%) observed in controls. Conclusions & Inferences: Dual expression of glial and neuronal markers in rectal and perirectal neurons support a model of Schwann cell‐derived neurogenesis in the innervation of the human GI tract. Abstract : In this paper, we describe double‐labeled neurons in the distal human GI tract suggesting a SC origin of enteric neurons as has been shown in rodents.